The Implementation of Two Stay Two Stray (TSTS) Learning Model in Reading Descriptive Text to Improve Reading Achievement - Sarah Mardatillah; Dio Resta Permana; Desi Suryatika (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
One of the obstacles to the learning process was the lack of interest in reading in students, especially in English texts. The design used in this study is Pre-Experimental with a sample of VIII.A consisting of 40 students. This study used pretest and post-test to collect data, which were analyzed using paired sample t-test with the help of SPSS version 23. Based on the results of this study, (1) there was a significant increase in students' reading comprehension achievement, (2) students gave a positive perception of the use of the Two Stay Two Stray (TSTS) method on reading comprehension skills of descriptive text in the learning process. In conclusion, the use of the Two Stay Two Stray (TSTS) method on reading comprehension skills of descriptive text can improve reading comprehension achievement of students in class VIII.